Nutrient management and medium reuse for cultivation of a cyanobacterial consortium at high pH and alkalinity - Paquette, Alexandre J.; Vadlamani, Agasteswar; Demirkaya, Cigdem; Strous, Marc; De la Hoz Siegler, Hector (Frontiers in Bioengineering and Biotechnology, 2022)
Alkaliphilic cyanobacteria have gained significant interest due to their robustness, high productivity, and ability to convert CO2 into bioenergy and other high value products. Effective nutrient management, such as re-use of spent medium, will be essential to realize sustainable applications with minimal environmental impacts. In this study, we determined the solubility and uptake of nutrients by an alkaliphilic cyanobacterial consortium grown at high pH and alkalinity. Except for Mg, Ca, Co, and Fe, all nutrients are in fully soluble form. The cyanobacterial consortium grew well without any inhibition and an overall productivity of 0.15 g L-1 d-1 (AFDW) was achieved. Quantification of nutrient uptake during growth resulted in the empirical formula CH1.81N0.17O0.20P0.013S0.009 for the consortium biomass. We showed that spent medium can be reused for at least five growth/harvest cycles. After an adaptation period, the cyanobacterial consortium fully acclimatized to the spent medium, resulting in complete restoration of biomass productivity.